The implementation evaluation of school-industry cooperation to strengthen the vocational school students’ competence - Azizah Nurul Husnaini; Budi Santosa; Tri Kuat (Universitas Ahmad Dahlan, 2021)
This research aims to conduct an evaluation of the implementation of school-industry cooperation in form of internship program. The evaluation focused on the aspects of (1) context in terms of the purpose of the agreement, (2) input in terms of readiness of cooperation, (3) process in terms of the quality of implementing cooperation, and (4) product in terms of benefits gained from school partner industry cooperation to strengthen the vocational students’ competencies. This research is an evaluation research viewed from the Context, Input, Process, and Product (CIPP) components. The research data were obtained from a questionnaire given to students, supervisors, internship working group teams, and school industry partners of the Electric Power Installation Engineering Department of SMK Negeri 1 Windusari. The results are, (1) the context variable got a positive result, (2) the input variable got a negative result, (3) the process variable got a negative result, and (4) the product variable got a negative result. Therefore, the CIPP evaluation found positive, negative, negative, negative (+ - - -) which made the CIPP variable is included in quadrant III of the Glickman quadrant. Thus, we found that implementation of school-industry cooperation to strengthen the students’ competence was less effective. The school could use these findings to improve the performance of the cooperation implementation.